The Fourth Industrial Revolution and the Importance of Disagreement - Alex Broadbent (The Thinker)
In healthy dialogue, there are always people who disagree, even if they are eccentric flat-Earthers. Something about human psychology seems to require that some people always take up a contrary position to the majority on any substantive idea, and empirical evidence always permits this, because it always underdetermines the conclusions we draw from it. When there is no disagreement on a certain idea, therefore, we have to consider that we’re either not assessing the idea properly, or not entertaining all opinions. If we were, some of us would come to different conclusions.